Influência das empresas de auditoria independente em escolhas contábeis de companhias brasileiras de capital aberto - Pinto, Aline Fernandes (2019)
The present study aims to verify the association between independent auditing companies and accounting choices. The sample consisted of 135 Brazilian companies listed in B3 from 2010 to 2017. The accounting choices regarding the measurement of investment properties, inventory measurement, depreciation rate, depreciation method, operating lease, recognition of purchases or regular sales of financial assets, classification of interest expense, classification of dividends and interest on own capital paid and dividends and interest on own capital received. To test the association between audit firms and accounting choices, the Chi-square test was used. The results indicate the association of the change of the audit firm with the change in accounting practices related to the measurement of investment properties, depreciation rate, depreciation method, recognition of the operational lease installments, recognition of purchases or regular sales of assets of classification of interest expense and dividends and interest on own capital received. Additionally, it was verified that the fact that the audit firm is a Big Four is associated with changes in practices related to the measurement of investment properties, inventory measurement and the classification of dividends and interest on own capital paid. Considering these results, it is understood that the audit can be considered as a relevant factor for the study of the accounting choices.